Pedagogical change and innovation culture in secondary education: a Delphi study - Valverde-Berrocoso, Jesús; Rivas-Flores, José Ignacio; Anguita-Martínez, Rocío; Montes-Rodríguez, Ramón (Frontiers in Education, 2023)
Secondary education in Spain is being the most controversial educational stage in educational reform processes, in relation to youth cultures and ways of learning and knowing in the emerging digital society. We present the results of the application of a Delphi methodology, as the first phase of a broader research on disruptive practices in Secondary Education. Its aim was to gather the opinion of 20 experts on how educational innovation processes are perceived at this educational level, as well as the mediations on which they are based. The Delphi questionnaire was applied in 3 Spanish regions (Andalusia, Castile and Leon, Extremadura) and was carried out in two consecutive rounds. Subsequently, focus groups were held with these experts in each of the regions. The results are grouped around 4 axes: the school institution, learning in non-formal contexts, educational innovation and innovation culture, and technological mediation. The conclusions reveal the main limitations of Secondary Education in Spain: lack of curricular flexibility, leadership for change and openness to the community, technocentric vision of educational innovation and insufficient training in digital competence of teachers.